Dynamically tuning near-infrared-induced photothermal performances of TiO2 nanocrystals by Nb doping for imaging-guided photothermal therapy of tumors. Issue 26 (26th June 2017) - Yu, Nuo; Hu, Yong; Wang, Xiaoyong; Liu, Gang; Wang, Zhaojie; Liu, Zixiao; Tian, Qiwei; Zhu, Meifang; Shi, Xiangyang; Chen, Zhigang
Abstract : We modulated the photothermal performance of TiO2 by Nb doping as novel theranostic nanoagents for tumor treatment. Abstract : Conventional wide bandgap semiconductors can absorb UV/visible light but have no photoabsorption band in the near-infrared (NIR) region, leading to difficulty in their use as NIR-responsive agents. With TiO2 as an example, we report the tuning from UV-responsive TiO2 nanocrystals to blue TiO2 nanocrystals with newly appeared NIR absorption band through the Nb-doping strategy. A strong NIR band should result from the localized surface plasmon resonances due to the considerable free electrons originating from the efficient incorporation of Nb 5+ ions (<15.5%). Interestingly, under the irradiation of a 1064 nm laser, Nb-doped TiO2 nanocrystals can convert laser energy into heat, and higher Nb-doping content can lead to higher NIR-induced temperature elevation, highlighting that the photothermal performances of TiO2 nanocrystals can be dynamically modulated by adjusting the Nb-doping levels. After coating with PEGylated phospholipid, the resulting nanocrystals display water dispersibility, high photothermal conversion efficiency and cytocompatibility. Therefore, these Nb-doped TiO2 nanocrystals can be used as efficient and heavy-metal-free nanoagents for the simultaneous NIR/photoacoustic imaging and photothermal therapy of tumors using a 1064 nm laser in the second biological window.